Answer: First Option
[tex]\frac{x(x-4)(x-1)}{2(x+4)}[/tex]
Step-by-step explanation:
We have the following expression
[tex]\frac{x^2-16}{2x+8}*\frac{x^3-2x^2+x}{x^2+3x-4}[/tex]
First factorize the denominators:
[tex]\frac{x^2-16}{2(x+4)}*\frac{x^3-2x^2+x}{(x+4)(x-1)}[/tex]
Now we factor the numerators
[tex]\frac{(x-4)(x+4)}{2(x+4)}*\frac{x(x^2-2x+1)}{(x+4)(x-1)}[/tex]
[tex]\frac{(x-4)(x+4)}{2(x+4)}*\frac{x(x-1)^2}{(x+4)(x-1)}[/tex]
now we simplify the expression
[tex]\frac{(x-4)}{2}*\frac{x(x-1)}{(x+4)}[/tex]
[tex]\frac{x(x-4)(x-1)}{2(x+4)}[/tex]
The answer is the first option
Answer:
A on Edge
Step-by-step explanation:
Good Luck!
An aerial camera is suspended from a blimp and positioned at D. The camera needs to cover 125 meters of ground distance. If the camera hangs 10 meters below the blimp and the blimp attachment is 20 meters in length, at what altitude from D to B should the camera be flown?
A blimp over triangle EDF with height of 10 meters and FE equals 20 meters and triangle ADC with height BD and AC equals 125 meters. Triangles share point D.
A. 31.25 m
B. 62.5 m
C. 150 m
D. 250 m
Answer:
B. 62.5 m
Step-by-step explanation:
∠EDF and ∠ADC are vertical angles, and therefore equal.
EF and AC are parallel, so ∠DEF and ∠DAC are alternate interior angles, as well as ∠DFE and ∠DCA. Therefore, each pair is equal.
From this, we can say ΔDEF and ΔDAC are similar triangles. So we can write a proportion:
10 / 20 = DB / 125
DB = 62.5
Answer:
The correct option is B.
Step-by-step explanation:
Given information: In ΔEDF, FE=20 m and height = 10 m. In ΔADC, AC=125 m.
From the given information, we conclude that AC║EF.
In ΔEDF and ΔADC,
[tex]\angle E=\angle A[/tex] (Alternate interior angles)
[tex]\angle EDF=\angle ADC[/tex] (Vertically opposite angle)
By AA rule of similarity,
[tex]\triangle EDF\sim \triangle ADC[/tex]
The corresponding sides of two similar triangles are similar. So in ΔEDF and ΔADC,
[tex]\frac{base}{height}=\frac{FE}{h}=\frac{AC}{DB}[/tex]
[tex]\frac{20}{10}=\frac{125}{DB}[/tex]
[tex]2=\frac{125}{DB}[/tex]
On cross multiplication, we get
[tex]2DB=125[/tex]
Divide both sides by 2.
[tex]\frac{2DB}{2}=\frac{125}{2}[/tex]
[tex]DB=62.5[/tex]
Therefore the correct option is B.
Sat math. Only one question. I am not sure of the answer
Answer:
8
Step-by-step explanation:
To find Y, find X first. Multiply 2 by W (3) which is 6, and divide by 3, which gives us X=2. The inequality W+Z=X+Y substituted is 10=2+Y. Subtract 2 from 10 and you get Y=8
Answer:
13) 8
14) 2X or 4W/3 (depending on what the choices are)
Step-by-step explanation:
So I'm using the box given:
If then
W X W+Z=X+Y and 2W=3X
Y Z
13)
3 X 3+7=X+Y and 2*3=3*X
Y 7
To get W,X,Y, and Z I compared it to the first lay out and then replace the other W's,X's,Y's, and Z's.
So we have 3+7=X+Y which means 10=X+Y.
We also have 2*3=3*X which means 2=X (I divided both sides by 3).
If X=2 then 10=X+Y gives us 10=2+Y.
10=2+Y can be solved by subtracting 2 on both sides:
8=Y
Y=8
14)
W X W+W=X+Y and 2W=3X
Y W
So W+W=X+Y means 2W=X+Y
We are also given 2W=3X which means by substitution into the first equation we get 3X=X+Y.
3X=X+Y can be solved by subtracting X on both sides:
2X=Y
We can also write Y in terms of W.
We have 2W=3X so that means X=2W/3 (I divided both sides by 3)
Now I'm going to replace X in 2X=Y with (2W/3) giving me:
2(2W/3)=Y
4W/3=Y
What is the product?
(6r-1)(-8r3)
Answer:
[tex]\large\boxed{(6r-1)(-8r^3)=-48r^4+8r^3}[/tex]
Step-by-step explanation:
[tex](6r-1)(-8r^3)\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\=(6r)(-8r^3)+(-1)(-8r^3)\qquad\text{use}\ (a^n)(a^m)=a^{n+m}\\\\=-48r^{1+3}+8r^3\\\\=-48r^4+8r^3[/tex]
The product of the binomials (6r-1) and (-8r-3) is obtained using the FOIL method, and the final product is -48r² - 10r + 3.
To find the product of the binomials (6r-1) and (-8r-3), we use the distributive property (also known as the FOIL method). The FOIL method stands for First, Outer, Inner, Last, which refers to the multiplication of the respective terms in each binomial.
Applying the FOIL method:
First: Multiply the first terms in each binomial: 6r * -8r = -48r²
Outer: Multiply the outer terms in each binomial: 6r * -3 = -18r
Inner: Multiply the inner terms in each binomial: -1 * -8r = 8r
Last: Multiply the last terms in each binomial: -1 * -3 = 3
Now, combine the like terms (-18r + 8r = -10r) and write the final product: -48r² - 10r + 3
If C is the midpoint of segment AB and AB = 20, what is AC?
AB= 20 and AB is the full line.
We will have to divide the length of the segment by 2 to find AC.
20/2= 10
AC is 10 units. Hope this helps!
Answer: the answer is: AC= 10
Step-by-step explanation:
you can imagine a line that represents AB with 20cm of large and the midline is located in the middle of this line; this means that AC is the half of AB
So in number=
[tex]AC= AB/2[/tex]
replacin [tex]AB[/tex]
[tex]AC= 20/2[/tex]
[tex]AC=10[/tex]
In the triangle below, what is the measure of R?
Answer:
30
Step-by-step explanation:
(7-c)(-1)
Simplify the expression
I’ve been stuck on this for a while now and I can’t get through it can someone please help me please
Answer:
-7 +c
Step-by-step explanation:
(7-c)(-1)
Distribute the -1
-1*7 -1*(-c)
-7 +c
is 42 a multiple of 7
Answer:
yes
Step-by-step explanation:
7 * 6 = 42
In △ABC, m∠A=16°, m∠B=49°, and a=4. Find c to the nearest tenth.
Answer:
c=13.2 units
Step-by-step explanation:
step 1
Find the measure of angle C
Remember that the sum of the internal angles of a triangle must be equal to 180 degrees
so
A+B+C=180°
substitute the given values
16°+49°+C=180°
65°+C=180°
C=180°-65°=115°
step 2
Find the measure of c
Applying the law of sines
c/sin(C)=a/sin(A)
substitute the given values and solve for c
c/sin(115°)=4/sin(16°)
c=4(sin(115°))/sin(16°)
c=13.2 units
Solve the system of equations.
y= 6x-27
y= 4x - 17
a. (-5, 3)
b. (-3, -5)
C. (5, 3)
d. No solution
Answer:
C. (5, 3)Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}y=6x-27&(1)\\y=4x-17&(2)\end{array}\right\\\\\text{Substitute (1) to (2):}\\\\6x-27=4x-17\qquad\text{add 27 to both sides}\\6x=4x+10\qquad\text{subtract}\ 4x\ \text{From both sides}\\2x=10\qquad\text{divide both sides by 2}\\x=5\\\\\text{Put it to (2):}\\\\y=4(5)-17\\y=20-17\\y=3[/tex]
Create an equivalent system of equations using the sum of the system and the first equation
-3x + y = 12
x + 3y = 6
A.-3x + y = 12
- 2x + 4y = 18
B.-3x+y=12
-3x + 4y = 18
C -3x+y = 12
X + 4y = 18
D.-3x+y=12
-2x + 4y = 6
Answer:
[tex]\large\boxed{A.\ \left\{\begin{array}{ccc}-3x+y=12\\-2x+4y=18\end{array}\right}[/tex]
Step-by-step explanation:
[tex]\underline{+\left\{\begin{array}{ccc}-3x+y=12\\x+3y=6\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad-2x+4y=18\\\\\text{therefore}\\\\\left\{\begin{array}{ccc}-3x+y=12\\-2x+4y=18\end{array}\right[/tex]
Using the equation of the sum of the system of equations and the first equation of the system, the equivalent system of equations is:
-3x + y = 12
-2x + 4y = 18
(Option A)
Given the system of equations:
-3x + y = 12 ---> Eqn. 1 x + 3y = 6 ---> Eqn. 2Add Eqn. 1 and Eqn. 2 together:
-3x + y = 12
x + 3y = 6 (ADD)
-2x + 4y = 18
Therefore, using the equation of the sum of the system of equations and the first equation of the system, the equivalent system of equations is:
-3x + y = 12
-2x + 4y = 18
(Option A)
Learn more about equivalent system of equations on:
https://brainly.com/question/1869465
Geometry question
I got it right but I didn’t incorporate the 105
Was I supposed to ?
Answer:
See below.
Step-by-step explanation:
You didn't need to.
The angle adjacent to angle x = 45 degrees (alternate interior angle to the angle marked 45).
So x = 180 - 45 = 135 degrees.
Answer:
C. 135
Step-by-step explanation:
In the figure above, line M is parallel to line N. The value of x is 135.
x = 180 - 45 = 135
find the value of k for which the following system of equations has a unique solutions 1 . kx +2y= 5 , 3x+y=1
Answer:
If you choose any value for k other than 6, that will be give you the one solution.
If k=6, you have no solutions because the lines will be parallel.
Step-by-step explanation:
We are going to put each of this in y=mx+b where m is the slope and b is the y-intercept.
kx+2y=5
Subtract kx on both sides:
2y=-kx+5
Divide both sides by 2:
y=(-k/2)x+(5/2)
The slope is -k/2 and the y-intercept is 5/2
3x+y=1
Subtract 3x on both sides:
y=-3x+1
The slope is -3 and the y-intercept is 1.
We want the system to have one solution so we want the slopes to be difference.
So we don't want (-k/2)=(-3).
Multiply both sides by -2: k=6.
We won't want k to be 6.
find the permiter of the polygon PLEASE help
Check the picture below.
Answer:
P = 46cmStep-by-step explanation:
If the circle inscribed in a quadrilateral, then the sums of the opposite sides of the quadrilateral are the same.
Therefore we have the equation:
AB + CD = BC + AD
Therefore the perimeter of polygon ABCD is equal to
P = 2(AB + CD)
Substitute AB = 10.5cm, CD = 12.5cm:
P = 2(10.5cm + 12.5cm) = 2(23cm) = 46cm
1452 divided by 44 = (1452 divided by 4) divided by 11
This division problem uses the method of...
A. Fractions
B. Repeated Subtraction
C. Factors
D. The Distributive Property
Answer:
Option C is correct.
Step-by-step explanation:
We are given
1452 divided by 44 = (1452 divided by 4) divided by 11
We know that 44 = 4*11
So, 4 and 11 are factors of 44.
This division problem uses the method of Factors.
Option C is correct.
Please help me thank you sooo much
Answer:
Step-by-step explanation:
Firstly you must understand you want to get the value of y.
So put in values into equation which make x.
To understand here lets look at y = 0
if y is to be 0 then x is 3.
If we substitute this value into equation (B) we get the result.
Now we have identified our answer, all is left is to substitute all other values of x and see if y are true.
So , we can see B is the answer
Answer: B
Step-by-step explanation:
The answer has to be either A, or B, because when x input is negative, the y input is positive. Visa versa.
Then just input x and y into the equation to see which answer is correct.
First let’s do A: 12=-2(-3)-6
12=6-6
12 doesn’t equal 0, so A is incorrect
So then B is the obvious solution, but let’s solve it to make sure: 12=-2(-3)+6
12=6+6
This equation is true, so the answer is B
a diagnol of a cube measures 15 cm and the length of an edge is 75 square root.What is the length of the diagnol of a face of the cube? Round to the nearest tenth
A. 7.1
B. 12.2
C. 13
D. 15
Answer:
B: 12.2cm
Step-by-step explanation:
Got it right on edge 2021✅
Consider the quadratic function f(x)=8x2−7x+6. What is the constant of the function?
Answer:
6 is constant of the function .
Step-by-step explanation:
Given : f(x)=8x²−7x+6.
To find : What is the constant of the function?
Solution : We have given that f(x)=8x²−7x+6.
Standard quadratic equation : ax² +bx +c = 0.
Here,
a is the coefficient of x² and b is the coefficient of x .
c = constant.
Hence on comparing with it standard quadratic equation
Here, 6 is constant.
Therefore, 6 is constant of the function .
What is the equation of a line that passes through the point (0, -2) and has a slope of -3?
Answer: Y = -3x-2
Step-by-step explanation:
if there are two co-ordinates (x1,y1) and (x2,y2).
If the line is passing through these co-ordinates
Then Slopw of the line = (y2-y1)/(x2-x1)
We have one co-ordinate (-0,-2) let it be (X1,Y1)
Let second co-ordinate be (X,Y)
Slope = -3 = (Y-(-2)) / (X-0)
-7 = (Y+2)/(X)
Y+2 = -3 (X)
Y+2 = -3X
ADDING -2 ON BOTH SIDES OF THE EQUATION
Y+2-2 = -3X-2
Y = -3x-2
Perform the indicated operation.
g(t) = 2t + 2
h(t) = t^2 - 2
Find (g•h)(-3)
A.62
B.14
C.16
D.126
Answer:
C
Step-by-step explanation:
Substitute t = - 3 into h(t), then substitute value obtained into g(t)
h(- 3) = (- 3)² - 2 = 9 - 2 = 7, then
g(7) = (2 × 7) + 2 = 14 + 2 = 16 → C
Solve -2/3 x > 8 or -2/3x <4
I doubt it says "or". It's probably an and.
[tex]\dfrac{-2}{3}x > 8\wedge\dfrac{-2}{3x} < 4[/tex]
[tex]-2x > 24\wedge3x < \dfrac{4}{-2}[/tex]
[tex]x > -12\wedge x < -\dfrac{2}{3}[/tex]
[tex]\Rightarrow\boxed{-12 < x < -\dfrac{2}{3}}[/tex]
[tex]\Rightarrow\boxed{x\in(-12,-\dfrac{2}{3})}
[/tex]
Hope this helps.
r3t40
Answer:
{x | x < -12 or x > -6}
Graph the line with slope -1/3 and y-intercept-3.
Answer:
The graph in the attached figure
Step-by-step explanation:
we know that
The equation of the line into slope intercept form is equal to
[tex]y=mx+b[/tex]
where
m is the slope
b is the y-intercept
In this problem we have
[tex]m=-\frac{1}{3}[/tex]
[tex]b=-3[/tex]
substitute
[tex]y=-\frac{1}{3}x-3[/tex]
To graph the line find out the intercepts
Find the y-intercept
The y-intercept is the value of y when the value of x is equal to zero
so
For x=0
[tex]y=-\frac{1}{3}(0)-3=-3[/tex]
The y-intercept is the point (0,-3) -----> is a given value
Find the x-intercept
The x-intercept is the value of x when the value of y is equal to zero
so
For y=0
[tex]0=-\frac{1}{3}x-3[/tex]
[tex]x=-9[/tex]
The x-intercept is the point (-9,0)
Plot the intercepts and join the points to graph the line
see the attached figure
To graph the line with a slope of -1/3 and a y-intercept of -3, plot the y-intercept at (0, -3) and use the slope to find additional points. Connect the points to graph the line.
Explanation:To graph the line with a slope of -1/3 and a y-intercept of -3, we can start by plotting the y-intercept at the point (0, -3). Then, using the slope, we can find additional points on the line. Given that the slope is -1/3, we can move down 1 unit and to the right 3 units from the y-intercept to find the next point. We can continue this process to find more points and then connect them to graph the line.
Learn more about Graphing a line with slope and y-intercept here:https://brainly.com/question/35469586
#SPJ3
How much more will the total cost of three adult tickets be than three children tickets? (SHOW WORK) (Table at bottom)
Book Exhibition
Ticket | Cost
Adults | $22
Children | $15
Seniors | $14
Step-by-step explanation:
cost of adult ticket, AT = $22
Cost of child ticket, CT = $15
Difference in price, D = AT-CT = 22-15 =$7
Difference in price for 3 tickets = 3D = $21
Answer:
Three Adult Tickets will be $22 more than Three Children's Ticket
Step-by-step explanation:
One Adult= $22
One Child =$15
Three adults= $22 x 3= $66
Three Children= $15 x 3= $45
$66 - $45= $21
Sn=7k=1Σ[1+ (k-1)(2)]
Answer:
49
Step-by-step explanation:
I think I have read this right!
You let me know if you did not mean to write the following:
[tex]\sum_{k=1}^{7}(1+(k-1)(2)[/tex]
Alright so the lower limit is 1 and the upper limit is 7.
All this means is we are going to use the expression 1+(k-1)(2) and evaluate it for each natural number between k=1 and k=7 and at both k=1 and k=7.
The sigma thing means we add those results.
So let's start.
Evaluating the expression at k=1: 1+(1-1)(2)=1+(0)(2)=1+0=1.
Evaluating the expression at k=2: 1+(2-1)(2)=1+(1)(2)=1+2=3.
Evaluating the expression at k=3: 1+(3-1)(2)=1+(2)(2)=1+4=5.
Evaluating the expression at k=4: 1+(4-1)(2)=1+(3)(2)=1+6=7.
Evaluating the expression at k=5: 1+(5-1)(2)=1+(4)(2)=1+8=9.
Evaluating the expression at k=6: 1+(6-1)(2)=1+(5)(2)=1+10=11.
Evaluating the expression at k=7: 1+(7-1)(2)=1+(6)(2)=1+12=13.
Now for the adding!
1+3+5+7+9+11+13
4+ 12+ 20+13
16+ 33
49
stan cut two pieces of crown molding for his family room that were 8 feet 7 inches and 12 feet 11 inches. what was the total length of the molding?
Answer:
The total length of the molding is 21 feet and 6 inches
Step-by-step explanation:
* Lets explain how to solve the problem
- The length of the two pieces are 8 feet 7 inches and 12 feet 11 inches
- Each foot has 12 inches
- Lets change the lengths of the two pieces to inch
# First piece 8 feet 7 inches
∵ 1 foot = 12 inches
∴ 8 feet 7 inches = 8 × 12 + 7
∴ 8 feet 7 inches = 96 + 7
∴ 8 feet 7 inches = 103 inches
# Second piece 12 feet 11 inches
∵ 1 foot = 12 inches
∴ 8 feet 7 inches = 12 × 12 + 11
∴ 8 feet 7 inches = 144 + 11
∴ 8 feet 7 inches = 155 inches
- To find the total length add the two answers
∴ The total length of the molding = 103 + 155 = 258 inches
- Divide the answer by 12 to change it to feet
∵ 258 ÷ 12 = 21.5 feet
- To change it to feet and inch multiply 0.5 feet by 12
∵ 0.5 × 12 = 6 inches
∴ The total length of the molding is 21 feet and 6 inches
MARKING BRAINLIEST!!! Please help..
Karen is trying to choose a cellphone plan. Company J charges a subscription fee of $30 per month plus $1 per hour of use.
Company K charges no monthly fee, but charges $3 for every hour of use. Karen made this graph to compare the prices of the two plans....
The lines for company J and company K cross a point.
The coordinate (30,60) is the point at which company J and company K cost the same. What does the point (30,60) mean? (Hint: What is being graphed on the x-axis?
What is being graphed on the Y-axis?).
If Karen used her cell phone for less than 30 hours a month, which company should Karen choose? Why?
IF Karen uses her cell phone for more than 30 hours a month which company should she use? Why?
1. 12 mph, 24 miles
2. m=4, y=22
3.15/1, $1500
4. x=30 y=60, k cheaper, j cheaper
12.03,1.2,12.3,1.203,12.301 order least to greatest
Answer:
1,2, 1,203, 12,03, 12,3, 12,301
Step-by-step explanation:
1,2 → 1,200
1,203
12,3 → 12,300
12,301
I am joyous to assist you anytime.
Ordered from least to greatest:
1.21.20312.0312.312.301Solve x2 - 8x - 9 = 0.
Rewrite the equation so that it is of the form
x2 + bx = c.
Answer:
I just got done doing this. Full answers to all 4 problems are down below. All correct answers are bolded.
Step-by-step explanation:
First problem: x2 + -8 x = 9
Add 16 to each side x2 – 8x = 9 to complete the square.
Now that you have x² - 8x + 16 = 9 + 16, apply the square root property to the equation. Answer: (x – 4)² = 25
Choose the solutions to the quadratic equation x2 – 8x – 9 = 0. Answer: -1, 9
The equation x² - 8x - 9 = 0 can be written as x² +(-8x) = 9 which is of the form x² + bx = c where,
b = -8
c = 9
What are equations?An equation is a mathematical statement which equate two algebraic expressions. An equation has an equal to (=) sign in between the expression.
How to rewrite the given equation in the given form?The given equation is
x² - 8x - 9 = 0.
⇒ x² - 8x = 9
⇒ x² +(-8x) = 9
So the given equation is written of the form x² + bx = c, where,
b = -8
c = 9
Find more about "Equations" here : https://brainly.com/question/1833682
#SPJ2
Use a half-angle identity to find the exact value of tan 165 degrees
Answer:
√3 - 2.
Step-by-step explanation:
Let A = 330 degrees so A/2 = 165 degrees.
tan A/2 = (1 - cos A) / sin A
tan 165 = (1 - cos 330) / sin 330
= (1 - √3/2) / (-1/2)
= -2(1 - √3/2)
= -2 + 2 * √3/2
= √3 - 2.
Answer:
[tex]\sqrt{3}[/tex] - 2
Step-by-step explanation:
Using the half- angle identity
tan( [tex]\frac{x}{2}[/tex] ) = [tex]\frac{sinx}{1+cosx}[/tex]
[tex]\frac{x}{2}[/tex] = 165° ⇒ x = 330°
sin330° = - sin30° = - [tex]\frac{1}{2}[/tex]
cos330° = cos30° = [tex]\frac{\sqrt{3} }{2}[/tex]
tan165° = [tex]\frac{sin330}{1+cos330}[/tex]
= [tex]\frac{-\frac{1}{2} }{1+\frac{\sqrt{3} }{2} }[/tex]
= - [tex]\frac{1}{2}[/tex] × [tex]\frac{2}{2+\sqrt{3} }[/tex]
= - [tex]\frac{1}{2+\sqrt{3} }[/tex]
Rationalise by multiplying numerator/ denominator by the conjugate of the denominator
The conjugate of 2 + [tex]\sqrt{3}[/tex] is 2 - [tex]\sqrt{3}[/tex], hence
tan 165°
= - [tex]\frac{2-\sqrt{3} }{(2+\sqrt{3})(2-\sqrt{3}) }[/tex]
= - [tex]\frac{2-\sqrt{3} }{4-3}[/tex]
= - (2 - [tex]\sqrt{3}[/tex] )
= - 2 + [tex]\sqrt{3}[/tex] = [tex]\sqrt{3}[/tex] - 2
x + 2y = 5 3x + 5y = 14 Solve the system of equations. (3, 1) (7, -1)
Answer:
{x,y} = {3,1}
Step-by-step explanation:
// Solve equation [1] for the variable x
[1] x = -2y + 5
// Plug this in for variable x in equation [2]
[2] 3•(-2y+5) + 5y = 14
[2] - y = -1
// Solve equation [2] for the variable y
[2] y = 1
// By now we know this much :
x = -2y+5
y = 1
// Use the y value to solve for x
x = -2(1)+5 = 3
Solution :
{x,y} = {3,1}
For this case we have the following system of equations:
[tex]x + 2y = 5\\3x + 5y = 14[/tex]
To solve, we multiply the first equation by -3:
[tex]-3x-6y = -15[/tex]
We add the equations:
[tex]-3x + 3x-6y + 5y = 14-15\\-y = -1\\y = 1[/tex]
We look for the value of the variable "x":
[tex]x + 2 (1) = 5\\x + 2 = 5\\x = 5-2\\x = 3[/tex]
Thus, the solution of the system is (3,1)
Answer:
(3,1)
Identify if the proportion is true or false. 4 to 11 = 12 to 33.
Answer:
True
Step-by-step explanation:
Take 4/11 and you get 0.363636363636, which is the same if you take 12/33. So the proportion of the two is the same.
Answer:
True
Step-by-step explanation:
To find out if the proportion is true you have to find out what multiplied by 4 equals 12.
To find that out you have to divide 12 by 4 which equals 3.
Now you have to do the same for the denominators. So, 33/11 equals 3.
The proportion is true because the numerator and denominator are both multiplied by 3 to get 12 to 33.